Wage Rigidity, Collective Bargaining, and the Minimum Wage: Evidence from French Agreement Data - Avouyi-Dovi, Sanvi; Fougère, Denis; Gautier, Erwan (The Review of Economics and Statistics, 2013)
Using data sets on wage agreements at both industry and firm levels in France, we document stylized facts on wage stickiness. The average duration of wages is a little less than one year, and 10% of wages are modified each month by a wage agreement. The frequency of wage change agreements is staggered over the year, but the frequency of effective wage changes is seasonal. The national minimum wage has a significant impact on the probability and the seasonality of wage changes. Negotiated wage increases are correlated with inflation, minimum wage increases, and firm profitability.